Modeling Student Mathematics Achievement in Senior High School Based on Selection Results Using Gee 2 Method with Natural Spline - Erfan Syahuri; I Made Tirta; Budi Lestari; Dian Anggraeni (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Every school has a vision and mission to become the superior institution so that it can compete and gain trust from the public. To achieve that, one of the efforts of the school is doing the selection of new students at the beginning of each academic year. In Lumajang region, admission of new students (PPDB) are selected using several components, such as national test scores (NUN) and Mapping/Placement test (MP). This research explores the best model of the relationship between selection components (and other conditions of students at the time of selection) and academic achievement during high school (in the form semester mathematics grade) starting from semester 1 till 5 at 3 schools in Lumajang regions. We apply Generalized Estimating Equation order 2 (GEE2) with Natural Spline. The results show that (i) the three schools, have different model and PGRI has the highest mean, followed by SMA1and SMA3, as shown by significant negative estimates of the coefficients. (i) Altough it is relatively small, distance from school has negatif contribution to the mathematics grade as shown by negatif (but significant) coefficient; (ii) The Junior High School NUN has nonlinear (and nonparametric) contribution as shown by the graphical representation and coefficient of natural spline. (iii) Score of Placement Test contribute positively and significantly to the the smester mathematics grade.